Galen and the Parchment Codex: A Note on the Text of De indolentia 33. - Nongbri, Brent (Classical Philology, 2025)
The publication in 2007 of a complete text of Galen's De indolentia has stimulated a renewed interest in Galen as a source for Roman book culture, especially the early history of the codex. One phrase at De indolentia 33 is particularly important in these discussions, διφθέρας πυκτάς ("fist-sized parchments"). In 2010, the Budé edition of De indolentia emended this phrase to read διφθέρας π<τ>υκτάς ("folded parchments"). This note argues that the emendation is unnecessary because the Greek phrase πυκταὶ διφθέραι is a sensible calque for the Latin pugillares membranei , which Martial used to describe parchment codices decades before Galen.